2016
DOI: 10.3892/mmr.2016.5688
|View full text |Cite
|
Sign up to set email alerts
|

Notch 2 signaling contributes to cell growth, anti-apoptosis and metastasis in laryngeal squamous cell carcinoma

Abstract: Notch signaling is important during the development of a variety of human tumors. Depending on the context, Notch signaling can be either oncogenic or anti-proliferative, and therefore, its effects in cancer are unpredictable. The aim of the present study was to identify the importance of Notch 2 in the cell growth and metastasis of laryngeal squamous cell carcinoma (LSCC). The current study performed quantum dots-based immunofluorescence histochemistry to determine expression of Notch 2 in 72 LSCC samples wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Previous studies revealed that laryngeal squamous cell carcinoma progression is associated with many signaling pathways, such as the NF-κB signaling pathway, 37 vitamin D receptor signaling pathway, 28 AKT signaling pathway, 27,33,38,39 and Notch2 signaling pathway. 40 Tra2β is involved in the activation of many signaling pathway, such as the Wnt signaling pathway 41 and HtrA/PED pathway. 42 However, no evidence demonstrated whether Tra2β could regulate the activation of the PI3K/AKT signaling pathway in LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that laryngeal squamous cell carcinoma progression is associated with many signaling pathways, such as the NF-κB signaling pathway, 37 vitamin D receptor signaling pathway, 28 AKT signaling pathway, 27,33,38,39 and Notch2 signaling pathway. 40 Tra2β is involved in the activation of many signaling pathway, such as the Wnt signaling pathway 41 and HtrA/PED pathway. 42 However, no evidence demonstrated whether Tra2β could regulate the activation of the PI3K/AKT signaling pathway in LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…NOTCH2 is involved in maintaining the proliferative state of NSCs and inhibiting differentiation [32]. It functions as a mitotic and an anti-apoptotic factor in other cell types also [33][34][35][36]. Further paired box (PAX) genes code for transcription factors, which contain a highly conserved DNAbinding domain called the paired domain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various factors have been revealed to be closely related with lymphatic metastasis of LSCC, such as Notch 2 [ 19 ], TRPP 2 [ 20 ], EZH 2 [ 21 ], MMP 9 [ 22 ], and DNRG 3 [ 23 ]. Because KAI1 and nm23 can influence tumor metastasis, we suspect that KAI1 and nm23 can be used as molecular markers in determining the lymphatic metastasis potential of LSCC.…”
Section: Introductionmentioning
confidence: 99%